Ken Lowder letter to Nicholas S. Halmi regarding spring bird sightings, June 5, 1979 - Lowder, Kenet al (1979)
Letter from Ken Lowder to Nicholas S. Halmi regarding spring bird sightings, June 5, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed